[tex]7\left(\frac{1}{2}\right) \div(-2)\left(\frac{5}{6}\right)[/tex] = [tex]\frac{45}{-7} \text { or }-6.4285[/tex]
Step-by-step explanation:
Given expression:
[tex]7\left(\frac{1}{2}\right) \div(-2)\left(\frac{5}{6}\right)[/tex]
[tex]\frac{7\left(\frac{1}{2}\right)}{(-2)\left(\frac{5}{6}\right)}[/tex]
The fraction [tex]7\left(\frac{1}{2}\right)[/tex] can be written by multiplying 7 with 2 and add to ‘1’. So,
[tex]7\left(\frac{1}{2}\right)=\frac{14+1}{2}=\frac{15}{2}[/tex]
The fraction [tex](-2)\left(\frac{5}{6}\right)[/tex] can be written by multiplying (-2) with 6 and add to ‘5’. So,
[tex](-2)\left(\frac{5}{6}\right)=\frac{-12+5}{6}=\frac{-7}{6}[/tex]
Applying these, we get
[tex]\frac{\frac{15}{2}}{\frac{-7}{6}}[/tex]
When do solving with numerator fraction, the denominator fraction [tex]\frac{-7}{6}[/tex] can be written as [tex]\frac{6}{-7}[/tex]. Therefore,
[tex]\frac{15}{2} \times \frac{6}{-7}=\frac{15 \times 3}{-7}=\frac{45}{-7}=-6.4285[/tex]